2020
DOI: 10.1038/s41598-020-68475-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of epinephrine on the perfusion index during ultrasound-guided supraclavicular brachial plexus block: a randomized controlled trial

Abstract: The perfusion index (PI) is an objective tool used to assess a successful nerve block. Epinephrine is a widely used adjuvant to local anesthetics, and it may affect PI values because of the vasoconstrictive property. The aim of this study was to investigate the influence of epinephrine on PI as an indicator of a successful block in ultrasound-guided supraclavicular brachial plexus block (SCBPB). In this randomized controlled trial, 82 adult patients underwent upper limb surgery under SCBPB were recruited betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…In order to prolong the time of single nerve block analgesia, more and more anesthesiologists add adjuvants to local anesthetics (LAs) [ 3 ]. Over the past decade, adjuvants of local anesthetics such as opioids [ 4 ], epinephrine [ 5 ], clonidine [ 6 ], magnesium [ 7 ], midazolam [ 8 ], dexamethasone [ 9 ], buprenorphine [ 10 ] and dexmedetomidine (DEX) [ 11 ] have been proved to prolong the analgesic time of nerve block, and have achieved varying degrees of success. Among these different kinds of adjuvants, DEX is more widely used.…”
Section: Introductionmentioning
confidence: 99%
“…In order to prolong the time of single nerve block analgesia, more and more anesthesiologists add adjuvants to local anesthetics (LAs) [ 3 ]. Over the past decade, adjuvants of local anesthetics such as opioids [ 4 ], epinephrine [ 5 ], clonidine [ 6 ], magnesium [ 7 ], midazolam [ 8 ], dexamethasone [ 9 ], buprenorphine [ 10 ] and dexmedetomidine (DEX) [ 11 ] have been proved to prolong the analgesic time of nerve block, and have achieved varying degrees of success. Among these different kinds of adjuvants, DEX is more widely used.…”
Section: Introductionmentioning
confidence: 99%
“…A recent work showed that PI performances for detection of regional block success were not different when using epinephrine as an adjuvant to local anaesthetics [43].…”
Section: Pi In Assessment Of Regional Block Successmentioning
confidence: 99%
“…Eighty-two patients were placed in 2 groups where one group received 12.5 mL of 2% lidocaine, 12.5 mL of 0.75% ropivacaine, and 0.1 mL of normal saline in the nonepinephrine group while the other group received 12.5 mL of 2% lidocaine, 12.5 mL of 0.75% ropivacaine, and 5mcg/mL of epinephrine in the epinephrine group. Using a pulse oximeter to assess the perfusion index, the study found the addition of epinephrine did not affect the perfusion index or perfusion index ratio during the block (P = 0.894 and P = 0.079, respectively) (61). All clinical studies are summarized below in Table 1.…”
Section: Clinical Studies: Safety and Efficacymentioning
confidence: 99%